Secular Trends and Technological Progress - Robin Döttling; Enrico Perotti (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
We study the redistributive effects of a gradual productivity shift from tangible to intangible capital. Intangible asset creation relies on the commitment of skilled human capital. To ensure retention,firms reward innovators by deferred compensation, so funding demand by firms drops as the importance of intangible assets rises. Since human capital income is not tradable,the supply of investable assets falls and innovator rents rise.The general equilibrium effect is a fall in interest rates, while surplus savings are stored in higher asset valuations. This shift leads to increasing inequality and skewness in both the capital and labor income share.Rising house prices and wage inequality lead to higher household leverage.
Keywords: D33; E22; G32; 330; Intangible capital; skill-biased technological change; human capital; excess savings; house prices